Improving Learning Outcomes on the Theme of My Dream by Using the Cooperative Learning Model Type Group Investigation in Fourth Grade Students of SD Negeri 027 Samarinda Ulu: Peningkatan Hasil Belajar Tema Cita-Citaku Dengan Menggunakan Model Cooperatif Learning Tipe Group Investigation Pada Siswa Kelas IV SD Negeri 027 Samarinda Ulu - Nur Agus Salim; Siska Oktaviani; Sani Ati (Borneo Educational Journal (Borju), 2023)
This study aims to reveal advance the learning outcomes of my aspirational themehow to develop the learning outcomes of my aspirational theme by using a cooperative group investigation cooperative model in class fourth grade 027 Samarinda Ulu. The formulation of the problem is how to improve the learning outcomes of my aspirational theme by using the cooperative learning group investigation model in fourth-grade students of SD Negeri 027 Samarinda Ulu. The group investigation model is one of the cooperative learning models that emphasizes the participation and activities. With this model, students attempted to find their own material or information to be learned through materials, for example, from books or the internet. Among the learning models created, group investigation is one of the learning models that is democratic because students become independence learner. Based on the results, the average value in round one 65.38 with a percentage of completeness 61.53% because in round I have not yet reached the greatest completeness criteria. The study continued in cycle II, in this cycle the average value obtained was 80 with a percentage of completeness of 84.61%. Based on the research results above, it can be concluded that the application of the cooperative learning group investigation model can improve the learning outcomes of my aspirational theme in fourth-grade students at SD Negeri 027 Samarinda Ulu.